Diversity and composition of plants, butterflies and odonates in an Imperata cylindrica grassland landscape in East Kalimantan, Indonesia. (4th October 2016) - Cleary, D.F.R.
Abstract: In Indonesia and elsewhere, Imperata cylindrica grassland now covers millions of hectares of land previously covered by rain forest. In the present study, shrubs, trees and climbers were recorded in sixteen 10 × 20-m plots and herb cover (ferns, grasses and herbaceous dicots) estimated in nested 2 × 2-m subplots. Butterflies and odonates were netted along 300-m transects. All plots and transects were randomly allocated to a 450 ha, I. cylindrica -dominated landscape. A total of 43 shrub, tree and climber, 16 herb, 67 butterfly and 30 odonate species were recorded. Shrubs, trees and climbers were present throughout the study area, but basal area was very low and mainly consisted of invasive species. Imperata cylindrica covered an estimated 65% of the area with other plant species or bare soil covering the remainder. Butterfly and odonate communities mainly consisted of species with large geographic distributions, but some recorded species had more limited distributions. The latter were, however, species known to associate with perturbed forest environments. Variation in the composition of butterflies and odonates was also related to variation in habitat structure (e.g. altitude and slope) and plant composition. Plant composition in particular appeared to structure both butterfly and odonate communities.